Stimulation of chondrocytes and chondroinduced mesenchymal stem cells by osteoinduced mesenchymal stem cells under a fluid flow stimulus on an integrated microfluidic device - Bao, Xuanwen (Mol Med Rep, 2018)
The aim of the present study was to investigate the stimulation of osteoinduced mesenchymal stem cells (MSCs) into chondrogenically predifferentiated MSCs and chondrocytes in a mechanical environment. A novel two-layer microfluidic chip was used to mimic the interstitial flow in the superficial zones of articular cartilage. The morphology, proliferation rate and the expression of collagen I, collagen II and aggrecan of chondrocytes and chondro-MSCs were investigated. The results revealed that the cells in the bottom layer were influenced by the top layer's osteoinduced MSCs and the bottom layer's shear flow. The expression of collagen I, which may signify the effect of the shear stress on the dedifferentiation change, was weakened by the stimulation of osteoinduced MSCs on the top layer. The expression of collagen II and aggrecan was increased in the fluidic environment by osteoinduced MSCs. These results indicate that osteoinduced MSCs have a significant effect on the phenotype of chondro-MSCs and chondrocytes in the fluidic microenvironment. The present study described a simple and promising way to rapidly evaluate cell responses to other cells in a fluidic environment, which may help to better promote the utilization of MSCs and chondrocytes in tissue engineering.